QARAQALPAQ TILINIŃ LINGVISTIKALÍQ KORPUS PLATFORMASÍN JARATÍW (Tólepbergen Qayıpbergenovtıń shıǵarmaları mısalında) - Abdalieva, G.R.; Uteuliev, N.U.; Kalmuratov, B.K.; Utesinova, A.S. (SCIENCE and SOCIETY, 2025)
This article focuses on the process of creating a linguistic corpus based on the Karakalpak language. Using T.Kaipbergenov's works as an example, it highlights methods for systematic language analysis and the potential of information systems. The importance of natural language processing technologies and linguistic corpora is analyzed as an innovative approach in linguistics. The article outlines the stages of corpus creation, its technical aspects, and its scientific and practical significance.
Keywords: karakalpak language; linguistic corpus; cultural heritage; morphological analysis; syntactic analysis; semantic analysis; lemmatization; tokenization; artificial intelligence; phraseology